Pengembangan Kualitas Produk Dalam Upaya Meningkatkan Volume Penjualan Produk Home Industry Madu Lebah Kelulut “Nano Alami” - Chandra, Rinaldi Aria; Irwansyah, Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
Product quality is seen as being able to influence product purchasing decisions by prospective consumers so as to increase the sales volume of a product. Previously, the "Nano Alami" kelulut bee honey home industry product experienced a decline in sales volume in 2022 due to the emergence of similar products under different brands, leading to market competition. It has become one of the driving factors for the "Nano Alami" kelulut bee honey home industry in developing product quality to increase product sales volume. So, this study aims to find out how product quality development is carried out to increase product sales volume. The research used is a qualitative method with the collection of data by observation, interview, and documentation techniques. Data analysis was carried out in three stages sequentially, they are data reduction, data presentation, and drawing conclusion.The results showed that the quality development of the home industry "Nano Alami" kelulut bee honey product which in the production system includes input processes, production processes, and output. In the input process, development is carried out using portable refractometer technology tools to measure water content in order to improve the quality of raw materials. Furthermore, in the production process, there are three development aspects which are carried out namely post-harvest by increasing the duration of the standing period to reduce water content; addition of variations of packaging bottles; as well as renewing packaging containers in the form of cardboard boxes which are specifically designed to increase security during product distribution. Besides, the output in in the form of improved products in order to increase the trust of potential customers, namely by including the product distribution permit number on the "Nano Alami" kelulut bee honey home industry. So that the development of product quality that has been carried out is able to support the increase in product sales volume. Keywords : Product Quality Development, Increase in Sales Volume, Home Industry